PENGEMBANGAN PERIKANAN TANGKAP BERBASIS CODE OF CONDUCT FOR RESPONSIBLE FISHERIES (CCRF) DI TERNATE, PROVINSI MALUKU UTARA - Julia Eka Astarini; John Haluan; Sugeng Hari Wisudo; Daniel Monintja; Domu Simbolon (Institut Pertanian Bogor, 2011)
This research was conducted in Ternate Waters which is located in Fisheries Management Zone or WPP 715 (Maluku Sea, Gulf of Tomini, and Ceram Sea). DKP and LIPI (2001) reported that the level of exploitation on fish resources in this area is just reach to about 41.83%. To assure a sustainable capture fisheries in this management area, a study based on Code of Conduct for Responsible Fisheries (CCRF) criteria is needed so that the fisheries potential resources could be optimally utilized, to contribute a significant role in the local economy and fisher’s prosperity. This study was aimed to (1) identifying fishing units which are supporting the CCRF’s criteria, (2) determining an optimal composition of fishing units to be developed. The research was conducted using survey method. Scoring method and Linear Goal Programming are among the method of analysis applied. The result of analysis shows that most of the fishing units operating in the area are still fulfillling the CCRF criteria. The analysis also shows the most favourable fishing units to be furtherly developed for the area in ranking order, subsequently are : the handline, pole and line, and purse seine. The optimal composition of fishing units to be developed in the research area are : the handline 751 units, pole and line 33 units, and purse seine 86 units.